Energy, emotional technology and cultural value of data – Creating user awareness through storytelling - Alessandro Valenti; Francesca Scalisi; Cesare Sposito; Laura Dellamotta; Alessandro Masserdotti (Agathón)
Design, understood as a modern discipline in its broadest sense, has always been inextricably linked to energy production, availability and accessibility. Every project resulting from human creativity and ingenuity, whether material or immaterial, analogue or digital, depends on it; it is necessary to break free from this atavistic dependence by finding alternative paths that lead us to the energy transition. An increase in human awareness is required to accomplish this and achieve social and environmental equity. In this perspective, this paper, starting with the concepts of ‘mitigation’, ‘sufficiency’, ‘circular economy’ and ‘innovability’, illustrates a number of highly replicable experiments carried out by the multidisciplinary Dotdotdot Studio by employing storytelling, emotive technology and the value of data to generate awareness in users on the issue of energy conservation.